2015
DOI: 10.48550/arxiv.1512.01219
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An eclipsing binary black hole candidate system in the blazar Mrk 421

E. Benitez,
J. I. Cabrera,
N. Fraija
et al.

Abstract: Removing outbursts from multiwavelength light curves of the blazar Mrk 421, we construct outburstless time series for this system. A model-independent power spectrum light curve analysis in the optical, hard X-ray and γ-rays for this outburstless state and also the full light-curves, show clear evidence for a periodicity of ≈ 310 days across all wavelengths studied. A subsequent full maximum likelihood analysis fitting an eclipse model confirms a periodicity of 310 ± 1 days. The power spectrum of the signal in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
1
0
0
Order By: Relevance
“…The more significant γ-ray QPO at 285 d in the source (see BD20), however, was not detected in the V-band light curves. Similarly, 310 d optical QPO seen after removing flares in the optical observations, including AAVSO data partly, reported by Benitez et al (2015) and the QPO with a characteristic timescale of ∼ 480 day in the rest frame, equivalent to observed ∼ 490 days, as reproted by Nilsson et al (2018) were not observed in the LSP analysis…”
Section: Quasi-periodic Oscillationssupporting
confidence: 59%
“…The more significant γ-ray QPO at 285 d in the source (see BD20), however, was not detected in the V-band light curves. Similarly, 310 d optical QPO seen after removing flares in the optical observations, including AAVSO data partly, reported by Benitez et al (2015) and the QPO with a characteristic timescale of ∼ 480 day in the rest frame, equivalent to observed ∼ 490 days, as reproted by Nilsson et al (2018) were not observed in the LSP analysis…”
Section: Quasi-periodic Oscillationssupporting
confidence: 59%